13C/12C breath test ratio after the ingestion of a meal naturally enriched with (13C)carbohydrates is a surrogate marker of insulin resistance and insulin sensitivity in children and adolescents with Type 1 Diabetes. (November 2020) - Marigliano, Marco; Schutz, Yves; Piona, Claudia; Tomasselli, Francesca; Tommasi, Mara; Corradi, Massimiliano; Olivieri, Francesca; Fornari, Elena; Morandi, Anita; Maffeis, Claudio
Highlights: T1D patients with higher % CHO oxidized have a better post-prandial glucose control. Insulin sensitivity (eGDR/ISS) and 13 C/ 12 C enrichment are directly correlated. 13 C/ 12 C breath test could be a simple marker of insulin sensitivity in T1D patients. Abstract: Aims: To test the hypotheses that exogenous carbohydrate oxidation affects postprandial glycaemic profiles and 13 C/ 12 C breath test could be used for estimating insulin resistance (IR) and insulin sensitivity (IS) in youths with Type 1 Diabetes (T1D). Methods: Non-randomized, cross-sectional study for repeated measures; fifteen youths (11–15 years) with T1D were enrolled. Respiratory exchanges were measured by indirect calorimetry after the ingestion of a mixed meal [13% protein, 29% fat, 58% carbohydrate (CHO; naturally enriched with [ 13 C]carbohydrates)]. Total and exogenous CHOs oxidation was calculated by indirect calorimetry and 13 C/ 12 C breath test. IR and IS were calculated using estimated Glucose Disposal Rate (eGDR) and Insulin Sensitivity Score (ISS). Results: The blood glucose Area Under the Curve (BG-AUC) was significantly associated with the amount of exogenous CHOs oxidized (r = −0.67, p < 0.02) when adjusting for CHOs intake and %fat mass. A direct correlation between eGDR and ISS with exogenous CHOs oxidized (r = 0.70, p < 0.02; r = 0.61, p < 0.05 respectively) and with the differential of 13 C/ 12 C enrichment in the expired at breath test (r = 0.59, p < 0.05; r = 0.62, p < 0.05), was found. Conclusions: Assessing the capacity to oxidize exogenous CHOs (estimated by the differential of 13 C/ 12 C enrichment in the expired air at the breath test) could be used as a non-invasive surrogate marker of IR and IS in youths with T1D.